Effects of Arm Swing in Lower Limb Muscle Activation and Coordination During Treadmill Walking - Teresa Rodríguez-Millán; Clara B. Sanz-Morère; Agnese Cherubini; Rocío Urrutia; Filipe Oliveira Barroso; José L. Pons; Jesús Tornero (Applied Sciences)
Arm swing is an inherent aspect of human locomotion that enhances lower limb (LL) muscle activation, which may explain its benefits for stroke rehabilitation over fixed-arm approaches. This study analyzed how restricting arm movement affects LL muscle coordination by comparing treadmill walking with arms (WWA) and walking with no arms (WNA) through muscle synergy analysis. Surface electromyography was recorded from eight LL muscles in ten healthy participants. Significant differences were found in muscle activity envelopes at 50% of the gait cycle (GC) for the Gluteus Medius, 0% and 100% GC for the Vastus Lateralis and Semitendinosus, and 25% GC for the Semitendinosus, Gastrocnemius Medialis, and Soleus. The Rectus Femoris and Vastus Lateralis showed higher variability and activation in WNA compared to WWA. Synergy analysis revealed four muscle synergies, with a median global variance of 95%. While spatial components were similar, temporal differences emerged at 0% GC for Synergy 1, 5% and 90% GC for Synergy 2, and 95% GC for Synergy 3 (p < 0.05). Our results suggest that arm swing influences LL muscle activity and coordination during walking. Future studies will aim at understanding the effects of arm swing in stroke rehabilitation, which could help design more effective gait rehabilitation protocols including arm swing.